2018
DOI: 10.1002/jum.14766
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Endoscopic Ultrasound‐Guided Fine‐Needle Aspiration for Assessing Suspected Deep Pelvic or Abdominal Recurrence in Gynecologic Cancer: A Feasibility Study

Abstract: Endoscopic ultrasound-guided FNA is a minimally invasive, feasible, and safe technique for confirming pelvic/abdominal recurrence of gynecologic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
3
0
0
Order By: Relevance
“…Comparable results have been reported in some international studies. Subtil et al ( 17 ) reported a diagnostic accuracy of 90.3% among 46 patients with gynecologic tumors and suspected recurrent pelvic metastases using EUS-FNA; this result was similar to our results. Fernández-Esparrach et al ( 18 ) concluded that EUS-FNA has a high diagnostic accuracy for perirectal recurrences of rectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Comparable results have been reported in some international studies. Subtil et al ( 17 ) reported a diagnostic accuracy of 90.3% among 46 patients with gynecologic tumors and suspected recurrent pelvic metastases using EUS-FNA; this result was similar to our results. Fernández-Esparrach et al ( 18 ) concluded that EUS-FNA has a high diagnostic accuracy for perirectal recurrences of rectal cancer.…”
Section: Discussionsupporting
confidence: 92%
“…José et al . 18 reported that the accuracy rate of EUS-FNA was as high as 95.4% when utilized to evaluate lesions that could not be reached by other imaging techniques, which is very similar to the conclusions drawn by other studies. 19…”
Section: Diagnostic Value Of Eus In Benign Pelvic Masses With Colorec...supporting
confidence: 84%
“…EUS-FNA is a minimally invasive, feasible, and safe examination method for the pelvic and abdominal recurrence of gynecological tumors. José et al 18 reported that the accuracy rate of EUS-FNA was as high as 95.4% when utilized to evaluate lesions that could not be reached by other imaging techniques, which is very similar to the conclusions drawn by other studies. Aline et al 22 verified the diagnostic value of EUS-FNA for colorectal endometriosis; however, their final result was different from their hypothesis, which may be attributed to several factors, including insufficient puncture times, insufficient lesion targeting, and lack of experience in the field cell pathology.…”
Section: Diagnostic Value Of Eus-derived Technologies For Colorectal ...supporting
confidence: 73%